2008
DOI: 10.2522/ptj.20070076
|View full text |Cite
|
Sign up to set email alerts
|

Use of Protection Motivation Theory, Affect, and Barriers to Understand and Predict Adherence to Outpatient Rehabilitation

Abstract: The screening tool used in this study may assist in identifying patients who are at risk for poor adherence and provide valuable information to enhance provider-patient relationships and foster patient adherence. However, it is recommended that more research be conducted to further understand the impact of variables on patient adherence and that the screening tool be enhanced to increase its predictive ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 30 publications
1
57
0
1
Order By: Relevance
“…Mechanistically, negative affect may constrict an individual's thought-action repertoire and self-regulatory behaviors (Moskowitz et al, 2012), thus hindering the ability to adhere to treatment recommendations. Therapeutic efforts to reduce negative mood may be effective in encouraging patient involvement in the treatment process (Tice et al, 2007;Grindley et al, 2008). Curiously, both Independent models = single IV; multivariable models = simultaneous IV's.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, negative affect may constrict an individual's thought-action repertoire and self-regulatory behaviors (Moskowitz et al, 2012), thus hindering the ability to adhere to treatment recommendations. Therapeutic efforts to reduce negative mood may be effective in encouraging patient involvement in the treatment process (Tice et al, 2007;Grindley et al, 2008). Curiously, both Independent models = single IV; multivariable models = simultaneous IV's.…”
Section: Discussionmentioning
confidence: 99%
“…20 We presume that, if individuals perceive a high threat and susceptibility to health problems and perceive treatment as effective and valued, their adherence to the treatment program will increase. Other studies 23,24 also demonstrated that rehabilitation beliefs are related to adherence to the sport-injury rehabilitation program. However, only a few investigators 18 examined the influence of injured athletes' perceptions of social support on their rehabilitation beliefs, and the association between hope and rehabilitation beliefs is still unknown.…”
mentioning
confidence: 94%
“…The personality test has the advantage of objectively evaluating a patient's personality and psychological condition and is of greater clinical use than an ambiguous assessment such as 'somewhat peculiar patient'. In addition, this relevant information can be shared with various physicians and other medical personnel, including nurses and physical therapists [19][20][21].…”
Section: Discussionmentioning
confidence: 99%